Triglyceride–Glucose Index Independently Predicts New-Onset Atrial Fibrillation After Septal Myectomy for Hypertrophic Obstructive Cardiomyopathy Beyond the Traditional Risk Factors - Wei, Zhipeng; Zhu, Enjun; Ren, Changwei; Dai, Jiang; Li, Jinhua; Lai, Yongqiang (Frontiers in Cardiovascular Medicine, 2021)
The triglyceride–glucose index is a valuable marker of insulin resistance. However, the predictive value of this index for postoperative atrial fibrillation in patients undergoing septal myectomy remains unclear. A total of 409 patients with hypertrophic obstructive cardiomyopathy who underwent septal myectomy were recruited in this study. The triglyceride–glucose index was calculated for all patients preoperatively. All patients underwent clinical data collection, blood sampling, and standard echocardiographic examinations during hospitalization. The prevalence of postoperative atrial fibrillation was approximately 15% in the present study. Multivariate logistic regression revealed that age (odds ratio [OR]: 1.053, 95% CI: 1.016–1.090, P = 0.004), hypertension (OR: 2.399, 95% CI: 1.228–4.686, P = 0.010), left atrial diameter (OR: 1.101, 95% CI: 1.050–1.155, P < 0.001), and triglyceride–glucose index (OR: 4.218, 95% CI: 2.381–7.473, P < 0.001) were independent risk factors for postoperative atrial fibrillation in patients undergoing septal myectomy. In receiver operating characteristic curve analysis, the triglyceride–glucose index could provide a moderate predictive value for postoperative atrial fibrillation after septal myectomy 0.723 (95% CI: 0.650–0.796, P < 0.001). Moreover, adding the triglyceride–glucose index to conventional risk factor model could numerically but not significantly increase our ability to predict postoperative atrial fibrillation (area under the receiver: 0.742 (0.671–0.814) vs. 0.793 (0.726–0.860), p = 0.065) after septal myectomy. In our retrospective cohort study, the triglyceride–glucose index was identified as an independent predictor of postoperative atrial fibrillation in patients undergoing septal myectomy.